2013
DOI: 10.7566/jpsj.82.013601
|View full text |Cite
|
Sign up to set email alerts
|

Γ3-Type Lattice Instability and the Hidden Order of URu2Si2

Abstract: We have performed ultrasonic measurements on single-crystalline URu 2 Si 2 with pulsed magnetic fields, in order to check for possible lattice instabilities due to the hybridized state and the hidden-order state of this compound. The elastic constant ðC 11 À C 12 Þ=2, which is associated with a response to the À 3 -type symmetry-breaking (orthorhombic) strain field, shows a three-step increase at H ! 35 T for H k c at low temperatures, where successive meta-magnetic transitions are observed in the magnetizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
27
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
7
27
1
Order By: Relevance
“…The tendency toward lattice instability with B 1g symmetry is most probably related with the Kondo physics. Interestingly, similar softening effect (of 0.7%) of the elastic constant (C 11 − C 12 )/2 in the same symmetry (B 1g ≡ Γ 3 ) has been reported below 120 K by ultrasound velocity measurements 31 . In addition, they show that this effect disappears when high magnetic field of 35 T is applied along the c axis.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The tendency toward lattice instability with B 1g symmetry is most probably related with the Kondo physics. Interestingly, similar softening effect (of 0.7%) of the elastic constant (C 11 − C 12 )/2 in the same symmetry (B 1g ≡ Γ 3 ) has been reported below 120 K by ultrasound velocity measurements 31 . In addition, they show that this effect disappears when high magnetic field of 35 T is applied along the c axis.…”
Section: Resultsmentioning
confidence: 57%
“…Raman scattering 30 mainly reported temperature dependence of the intensity of the fully-symmetric phonon mode and optical conductivity studies were mostly focused on the electronic properties. A more detailed study by ultrasonic measurements versus temperature and under high magnetic field 31,32 reported a softening of the elastic constant C 11 − C 12 below ∼ 120 K suggesting a B 1g -type (or Γ 3 ) lattice instability in connection with the Kondo cross-over. Quite recently, an anomalous phonon softening below T 0 in the [1,1,0] direction has been reported by inelastic neutron scattering 33 , calling on for further detailed studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the temperature dependence of elastic constant (C 11 À C 12 )/2 shows an anomalous softening 31,32 , but we point out that the elastic constants are also Q ¼ 0 quantities, which are hard to couple to the antiferroic high-rank mulitpole orders. This softening may be due to the incommensurate excitations found by neutron experiments 33 , which may also be related to the high-field incommensurate spin density wave phase identified above the critical field of hidden order 34 .…”
Section: Discussionmentioning
confidence: 94%
“…This indicates that the lowtemperature electronic state of URu 2 Si 2 exhibits a lattice instability with 3 symmetry (x 2 -y 2 -type) that is strongly related to the origin of the hybridized electronic state and the HO. 12 In the present work, we explore a wider temperature range from 1.5 to 116 K up to 61. 8 procedure described in more detail in Ref.…”
mentioning
confidence: 99%
“…8 procedure described in more detail in Ref. 12. For the present measurements, long-pulsed magnetic fields with a duration of ∼150 ms and a maximum field of 61.85 T have been used.…”
mentioning
confidence: 99%